Control of Translation in Cultured Cells: Continued Synthesis and Accumulation of Messenger RNA in Nondividing Cultures - Rudland, Philip S. (1974)
Nontransformed animal fibroblasts in tissue culture regulate total protein and ribosomal RNA synthesis coordinately with changes in the cellular growth state. Here it is shown that the amounts and rates of synthesis of cytoplasmic poly(A)-containing RNA, presumed to be mRNA, do not appreciably change with alterations in growth state. In nongrowing (resting) cultures of BALB/c 3T3 cells presumptive mRNA molecules predominantly accumulate as cytoplasmic ribonucleoprotein particles; the RNA from which can be chased into the polyribosomal structure upon activation of the resting cultures with animal sera. It is suggested that the decreased protein synthetic rate in resting as compared with growing cells is in part due to a failure of preexisting mRNAs to attach to ribosomes and that addition of serum to the tissue culture medium can partially overcome this translational lesion.